DETECTION OF mecC-POSITIVE Staphylococcus aureus (CC130-MRSA-XI) IN DISEASED EUROPEAN HEDGEHOGS (Erinaceus europaeus) IN SWEDEN - SHORE, ANNA; COLEMAN, DAVID; LAZARIS, ALEXANDROS (My University, 2013)
Recently, a novel mec gene conferring beta-lactam resistance in Staphylococcus aureus has been discovered. This gene, mecC, is situated on a SCCmec XI element that has to date been identified in clonal complexes 49, 130, 425, 599 and 1943. Some of the currently known isolates have been identified from animals. This, and observations of mecA alleles that do not confer beta-lactam resistance, indicate that mec genes might have a reservoir in Staphylococcus species from animals. Thus it is important also to screen wildlife isolates for mec genes. Here, we describe mecC-positive Staphylococcus aureus (ST130-MRSA-XI) and the lesions related to the infection in two diseased free-ranging European hedgehogs (Erinaceus europaeus). One was found dead in 2003 in central Sweden, and suffered from S. aureus septicaemia. The other one, found on the island of Gotland in the Baltic Sea in 2011, showed a severe dermatitis and was euthanised. ST130-MRSA-XI isolates were isolated from lesions from both hedgehogs and were essentially identical to previously described isolates from humans. Both isolates carried the complete SCCmec XI element. They lacked the lukF-PV/lukS-PV and lukM/lukF-P83 genes, but harboured a gene for an exfoliative toxin homologue previously described from Staphylococcus hyicus, Staphylococcus pseudintermedius and other S. aureus of the CC130 lineage. To the best of our knowledge, these are the first reported cases of CC130-MRSA-XI in hedgehogs. Given that one of the samples was taken as early as 2003, this was the earliest detection of this strain and of mecC in Sweden. This and several other recent observations suggest that CC130 might be a zoonotic lineage of S. aureus and that SCCmec XI/mecC may have originated from animal pathogens.
PUBLISHED
Keywords: Toxins; Hedgehogs; Methicillin-resistant Staphylococcus aureus; Neutrophils; Polymerase chain reaction; Staphylococcus; Staphylococcus aureus; Immunology, Inflammation & Infection